2005
DOI: 10.1510/icvts.2005.118935
|View full text |Cite
|
Sign up to set email alerts
|

Is skeletonised internal mammary harvest better than pedicled internal mammary harvest for patients undergoing coronary artery bypass grafting?

Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was whether skeletonised internal mammary artery (IMA) is better than pedicle IMA in coronary artery bypass grafting? Altogether 106 papers were found using the reported search, of which 12 presented the best evidence to answer the clinical question. The author, journal, date and country of publication, patient group studied, study type, relevant outcomes, results, and study weaknesses of these paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…1) Also, several observational studies have reported that skeletonized BIMA harvest reduced the incidence of DSWI to as low as 1%-2% from 10%-11% observed with the pedicled technique in diabetic patients. [6][7][8] Despite the reported advantages, skeletonized technique of IMA harvest has so far been used by a minority of surgical groups, 2,5,6,[8][9][10][11] especially in China. Data about the incidence of DSWI following skeletonized BIMA harvest and the impacts of skeletonized BIMA grafting on clinical outcomes came almost entirely from American, European, and Japanese published studies; nevertheless, data from Chinese patients were lacking.…”
mentioning
confidence: 99%
“…1) Also, several observational studies have reported that skeletonized BIMA harvest reduced the incidence of DSWI to as low as 1%-2% from 10%-11% observed with the pedicled technique in diabetic patients. [6][7][8] Despite the reported advantages, skeletonized technique of IMA harvest has so far been used by a minority of surgical groups, 2,5,6,[8][9][10][11] especially in China. Data about the incidence of DSWI following skeletonized BIMA harvest and the impacts of skeletonized BIMA grafting on clinical outcomes came almost entirely from American, European, and Japanese published studies; nevertheless, data from Chinese patients were lacking.…”
mentioning
confidence: 99%
“…Then dissection of the artery continues down toward the bifurcation of the vessel, avoiding the phrenic nerve and finally removing the artery from parasternal tissues and fascia down toward the 6th intercostal space. The resulting graft is about 3 cm longer than a pedicle graft and can have a larger conduit diameter and flow [10].…”
Section: Discussionmentioning
confidence: 99%
“…The internal thoracic vein joins the subclavian vein and is usually not divided although it may be. Additional ITA length can be gained by dividing the vein and dissecting the ITA from the subclavian vein when more ITA length is required as this maneuver can add up to 3 cm of length [16]. This length is gained by greater posterior positioning of the proximal ITA which normally is an anterior structure while its destination, usually the LAD, lies posterior to the in situ ITA, even though the LAD is an anterior structure on the heart.…”
Section: Left Internal Thoracic Artery Harvestingmentioning
confidence: 99%
“…It was also found to increase conduit length and in some reports free flow was greater [16]. With increasing experience and facility some surgeons expanded this technique to single ITA harvest.…”
Section: Left Internal Thoracic Artery Harvestingmentioning
confidence: 99%
See 1 more Smart Citation